ANALISIS MOTIVASI BELAJAR DAN KEMANDIRIAN BELAJAR MAHASISWA FAKULTAS TEKNIK UNIVERSITAS SINGAPERBANGSA KARAWANG SELAMA PEMBELAJARAN DARING - Putri, Nida Indria; Fitriani, Risma (2021)
At the college level, students are the ones who, for the sake of their future studies, are pursuing the path of education with expectation of success. Since the high value obtained is one measuring student performance, the average value called Index Point Average (GPA) is measured. Several factors influencing the GPA student's contribution to the achievement, one learning motivation. Gaya learns to be one of the variables that can influence students cumulatively in GPA. The learning style of teaching aids was also a trivial consideration in this situation. The fundamental concepts of education at the Open University (UT) require learners to study through the distance learning method, learning tasks independently. The students, learning independence, need such activity. Independent learning is the preparation of people who, with or without the support of others in terms of learning goals, learning strategies, and assessment of learning outcomes, are ready and able to learn on their own initiative.